Evaluation of Antigen-Specific IgM and IgG Production during an In Vitro Peripheral Blood Mononuclear Cell Culture Assay - Matsuda, Yoshiko; Imamura, Ryoichi; Takahara, Shiro (Frontiers in Immunology, 2017)
The recent attention given to diseases associated with memory B-cell (mBC)-produced antibodies (Abs) suggests the need for a similar in vitro assay to evaluate the functions of mBCs. Here we cultured peripheral blood mononuclear cells (PBMCs) with the intent to collect mBC-derived Abs in vitro and maintain their cell-cell contact-dependent interactions with helper T-cells. PBMCs were cultured with interleukin (IL)-21, CpG-oligodeoxynucleotides (ODN), phorbol myristate acetate (PMA), and phytohemagglutinin/leucoagglutinin (PHA-L) in 24-well flat-bottom plates (5×10^5 cells/well). A culture supernatant analysis of PBMCs from healthy donors (n=10) indicated that antigen-specific IgM Ab levels in a PBMC culture supernatant might be better able to demonstrate the antigen sensitization status in a smaller peripheral blood sample, compared to IgG because Epstein–Barr virus-specific IgM mBCs circulate peripherally at a significantly higher frequency once anti-viral humoral immunity has stabilized. Thus, our in vitro assay demonstrated the potential significance of antigen-specific IgM Ab production in the culture supernatants. Furthermore, an analysis of cultured PBMCs from allograft kidney recipients (n = 16) sensitized with de novo donor-specific human leukocyte antigen-specific Abs (DSAs) showed that IgM-type human leukocyte antigen (HLA)-specific Abs were detected mainly from the culture supernatants from PBMCs of patients with stable graft function, whereas IgG isotype HLA Abs were detectable only from patients with biopsy-proven antibody-mediated rejection. In other words, these IgG isotype Abs also represented an activated humoral immune response in vivo. Additionally, IgM- and IgG-expressing mBCs from healthy donors (n=5) were cultured with IL-21, CpG-ODN, and a supernatant produced by stimulating CD19+ B-cell-depleted PBMCs with PHA-L and PMA in 24-well flat-bottom plates (1×10^5 cells/well), and the resulting in vitro analysis provided some information regarding the biological processes of IgG and IgM mBCs in peripheral blood. Taken together, our findings suggest that antigen-specific Ab subtype analyses of supernatants from cultured PBMCs might more effectively and accurately reflect a patient's Ab-associated pathological condition versus than serum IgG and IgM levels.